Board characteristics, ownership structure and audit fees: evidence from Chinese listed companies - Wei, Qianhan (2017)
This paper contributes to corporate governance and audit studies by providing further insight to the relation between board features, ownership structure and audit price. My research considers both of agency theory and resource dependence theory and tests the influence of ownership structure on board governance and audit cost in particular context of Chinese security market, which is in the absence of sufficient obligation of the board or legal protection for investor. The study result proves a negative correlation between board size and audit fees, and a positive relationship between board remuneration and audit fees, which are in line with prior literature. Besides, it is suggested that the influence of board independence on audit quality is less obvious in the presence of block shareholders. Given the ownership nature in Chinese market, the paper compares governance environment and audit quality of state-owned enterprise and private enterprise. It is demonstrated that state-owned enterprises have higher motivation and ability to purchase expensive audit service.